(untitled) (Proceedings of Southern Federal University. Philology, 2018)
Yulia S. Dubkova (Sevastopol, Russian Federation) This article examines and characterizes some existing ideographic dictionaries, reveals their advantages and disadvantages. Systematization of abbreviation units related to the concept of «movement by air» is carried out, a model for creating an ideographic dictionary of abbreviations is proposed, based on ideographic blocks. In the basis of the model of the dictionary, the author suggests putting the ideographic principle of organizing semantic fields represented by abbreviation units. Key words: ideographic dictionary, abbreviation units, abbreviation fields, ideographic blocks.